Kamisama kiss. Vol. 16 - Suzuki, Julietta (Viz Media, 2014)
Back in feudal Japan, Akura-oh is getting frustrated with his best friend and rampage companion Tomoe. He correctly guesses that Tomoe is lovesick, and decides the best way to deal with it is to kill the object of his affection--Yukiji! And to make matters worse, when Nanami wears historical clothes, she looks an awful lot like Yukiji! Can she manage to preserve the past, save Tomoe, protect Yukiji and keep from getting killed?!